Monitoring of large B-cell lymphoma and T-zone lymphoma in a dog via flow cytometry. (September 2021) - Rosenbaum, Claire S.; Seelig, Davis M.; Burton, Erin N.; Gwynn, Angela D.; Granick, Jennifer; Able, Hannah R.
A 12-y-old, castrated male Pomeranian dog was presented because of mandibular lymph node (LN) enlargement. Physical examination and a complete blood count revealed generalized lymphadenopathy and moderate lymphocytosis. Fine-needle aspirate cytology revealed expansion of medium lymphocytes in the right mandibular LN and expansion of large lymphocytes in the left popliteal LN. Flow cytometry identified 2 aberrant lymphocyte populations in both LNs, namely a CD5+CD45− T-cell population, and a large CD21+ B-cell population. Flow cytometry of the peripheral blood revealed an identical population of aberrant CD45− T cells. The patient was diagnosed with concurrent T-zone lymphoma and leukemia, and B-cell lymphoma. Multi-agent chemotherapy was instituted, and serial clinical and flow cytometric analysis revealed complete remission of the neoplastic B cells, but persistence of the neoplastic T cells and persistent lymphadenopathy. This case affirms the diagnostic value of flow cytometry and reveals a unique limitation of the RECIST criteria.